Development and validation of digital leadership skills scale - Nadire Cavus; Seyedali Aghamiri; Nuriye Sancar (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The main aim of this study is to construct a digital leadership skills scale (DLS scale) to measure digital leadership skills. Moreover, by integrating the constructed scale into the existing model in the literature, we aimed to investigate the influence of the DLS scale on organisational factors, digital transformation, and enterprises' financial performance. Research Design & Methods: We used the quantitative research method to construct the DLS scale and to test the proposed model based on a sample of 701 active employees in enterprises. In the first stage of the study, we conducted the comprehensive validity and reliability analysis including content validity, construct validity based on explanatory factor analysis, reliability analysis via Cronbach's alpha, Spearman-Brown co-efficient, and retest reliability with Intraclass correlation and Pearson correlation coefficients, confirmatory factor analysis, and item analysis during the development process of the DLS scale. In the second stage, we integrated the digital leadership skills scale into the existing model as a factor and examined the overall compatibility and harmony of the integrated DLS scale items with the existing model. In the third stage of the study, we tested the proposed model with a linear regression analysis model. Findings: The comprehensive validity and reliability analysis results showed that the constructed DLS scale is valid and reliable. Moreover, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), reliability, item analysis, convergent, and discriminant validity analysis results indicated that the constructed DLS scale was harmoniously integrated with the existing model in the literature. Moreover, simple linear regression analysis results indicated that the constructed digital leadership skills scale influences organisational factors, digital transformation (DT), and enterprises' financial performance. Implications & Recommendations: With the constructed scale, it will be possible for enterprises undergoing digital transformation to measure their digital leadership skills. Moreover, by integrating this constructed DLS scale into the model that enterprises will use during their digital transformation process, they can enhance the effect of digital transformation on financial performance as well. In other words, using this proposed model, enterprises can gain useful insights into the process of digital transformation and make well-informed choices about the integration of DLS into their digital transformation plans. Contribution & Value Added: In this study, we constructed a novel scale to determine the digital leadership skills of the leaders who will lead the digital transformation process in enterprises. Moreover, we introduced to the literature a different model that can evaluate the effects of digital leadership skills on organisational factors, DT, and financial performance of enterprises in the digitalization process in enterprises by proposing a model that includes the constructed scale.
Keywords: C8; O3; 330; digital leadership skills; digital transformation; enterprises; financial performance; organisational factors